Analysis of Residual Fatigue Life on Jacket Platform Structure Due to Subsidence Effect - As Achmad Daffa Dhiya’udien Munaf; Nur Syahroni; Handayanu (International Journal of Offshore and Coastal Engineering, 2026)
Many oil and gas platforms in Indonesian waters, both those still operating and those that have passed the operating life limit (expired), experience subsidence events, especially in the jacket platform structure. Subsidence around these platforms is caused by massive oil and gas exploitation in producing hydrocarbon reservoirs. This phenomenon poses a risk due to intolerable wave loads, where the waves increase the risk of structural failure, which can impact platform operations. Changes in seabed conditions due to subsidence will also affect the cyclical wave loads received by the platform jacket structure. In this Final Project, the author will analyze the residual fatigue life of the jacket platform structure due to subsidence. This Final Project research aims to analyze the effect of subsidence on the fatigue life of the jacket platform structure. Tests were carried out using cumulative damage and fracture mechanics methods to predict the failure time of the components reviewed in the jacket platform structure under non-subsidence conditions and when subsidence occurs. The analysis results show that the fatigue life of the structure will be reduced when subsidence occurs. With the cumulative damage method, the fatigue life value of the non subsidence condition is 279 years, while the residual fatigue life of the structure in the subsidence condition is 59 years. Meanwhile, using the fracture mechanics method, the value of the fatigue life of the non-subsidence condition is 76 years, and the residual fatigue life of the structure in the subsidence condition is 41 years. These results show a significant decrease in the fatigue life of the structure.